2020
DOI: 10.1111/jorc.12353
|View full text |Cite
|
Sign up to set email alerts
|

The work environment of haemodialysis nurses and its mediating role in burnout

Abstract: Background The work environment can contribute to the occurrence of nurses' burnout. Objectives This study assessed the work environment of haemodialysis nurses and the extent of burnout they have suffered, and it explored the connection between work environment and burnout. Design A multicentre cross‐sectional study was conducted in 53 public, hospital‐based haemodialysis units in Greece. Participants A total of 537 haemodialysis nurses participated. The majority consisted of females (90.8%) who possessed a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…A current study shows that social support in the work environment and supervision opportunities for trainees are key predictors of burnout and job satisfaction (Plantiveau et al, 2018). Clinically, a cross-sectional study in Greece concludes the work environment of hemodialysis nurses is associated with burnout (Moisoglou et al, 2020). Another study indicates the impact of work environment on burnout is greater than that of facility and individual characteristics among nursing directors in smaller hospitals (Takemura et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 82%
“…A current study shows that social support in the work environment and supervision opportunities for trainees are key predictors of burnout and job satisfaction (Plantiveau et al, 2018). Clinically, a cross-sectional study in Greece concludes the work environment of hemodialysis nurses is associated with burnout (Moisoglou et al, 2020). Another study indicates the impact of work environment on burnout is greater than that of facility and individual characteristics among nursing directors in smaller hospitals (Takemura et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 82%
“…Previous research has reported that working within better work environments could increase nurses' job satisfaction and decreases their intention to leave and burnout (Nantsupawat et al, 2017). More recently, Moisoglou et al (2020) found a negative association of healthy work environment with nurses' personal, work-related and patient-related burnout.…”
Section: Discussionmentioning
confidence: 97%
“…( 43 ) Staff in many locations will also have had to deal with the additional burden of providing consults and acute dialysis services to people with acute kidney injury associated with SARS-CoV-2 infection, and potentially having had to ration treatment. ( 44 ) The COVID-19 pandemic has put unprecedented pressures on healthcare services and professionals, not least those providing care to people with kidney disease, ( 39 , 45 ) yet psychological support services were only available in about half of surveyed centres.…”
Section: Discussionmentioning
confidence: 99%